Training needs: how SMEs increase their competitiveness study from small medium enterprises in the Yogyakarta Special Region” - Akhbar, Taufik; Darsono, Susilo Nur Aji Coko; Mohd Thas Thaker, Mohamed Asmy; ., Hendar; Ari Anggara, Fajar Surya (UMY Press, 2020)
This chapter aims to describe the readiness of SMEs in Yogyakarta Special Region Province facing global challenge in business in the future. Training is one method to ensure that business players of SMEs are ready to increase competitiveness. This chapter used qualitative research design and utilized questionnaire. Data for Small Medium Enterprises in Yogyakarta were col-lected from Small Medium and Enterprise Bureau. The findings of this chap-ter showed that in today’s prevailing conditions, SMEs mostly need training in management aspects because of the lack of knowledge in management. Most of the business players realize the need for training to increase their competitiveness in the future, not only in the management aspects for busi-ness processes, but also for the improvement of quality and the application of green technology in facing the Industrial Revolution.